2017
DOI: 10.3892/etm.2017.5013
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17 downregulates expression of the PTEN gene to promote the occurrence and development of adenomyosis

Abstract: Abstract. The aim of the current study was to evaluate the expression of microRNA (miR)-17 in the endometrial tissues of patients with adenomyosis (AM) and determine its biological function in the occurrence and development of the disease. A total of 45 fresh endometrial tissues of AM patients and 32 normal endometrial tissues were collected from healthy controls. The expression of miR-17 was evaluated using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The miR-17-targeting gene phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
1
25
0
2
Order By: Relevance
“…In adenomyosis, Ki-67 is expressed in the glandular epithelium of the ectopic endometrium and myometrial cells associated with hyperplasia and hypertrophy, irrespective of the menstrual phases (36)(37)(38). The genes and pathways involved in the regulation of apoptosis have been shown to be aberrantly expressed in the endometrium of women with adenomyosis, compared to the controls (39). We found that the survival and apoptosis-related genes were upregulated or downregulated in the previous studies cited.…”
Section: Functional Pathways Of Adenomyosis Candidate Genessupporting
confidence: 46%
See 1 more Smart Citation
“…In adenomyosis, Ki-67 is expressed in the glandular epithelium of the ectopic endometrium and myometrial cells associated with hyperplasia and hypertrophy, irrespective of the menstrual phases (36)(37)(38). The genes and pathways involved in the regulation of apoptosis have been shown to be aberrantly expressed in the endometrium of women with adenomyosis, compared to the controls (39). We found that the survival and apoptosis-related genes were upregulated or downregulated in the previous studies cited.…”
Section: Functional Pathways Of Adenomyosis Candidate Genessupporting
confidence: 46%
“…Thus, the proliferation-and growth-related genes, including IGF1 (16)(17)(18)(19), IGF2 (19), vascular endothelial growth factor (VEGF) (40)(41)(42), hepatocyte growth factor (HGF) (43)(44)(45), nerve growth factor (NGF) (46)(47)(48), platelet-derived growth factor (PDGF) (16,49), epidermal growth factor receptor (EGFR) (16,17,49,50), fibroblast growth factor 2 (FGF2) (49,51,52) and mechanistic target of rapamycin kinase (mTOR) (53,54), were upregulated in both the ectopic and eutopic endometria from subjects with adenomyosis compared with the eutopic endometria from women without adenomyosis, while the anti-apoptotic or autophagy-related genes, such as BCL2 apoptosis regulator (BCL2) (38,(55)(56)(57), beclin 1 (BECN1) (58,59) and programmed cell death 4 (PDCD4) (60,61), were much higher in the ectopic and eutopic endometria than in the control endometria. Furthermore, the decreased expression of BCL2 associated X, apoptosis regulator (BAX) has been observed in adenomyosis, suggesting that the downregulation of apoptotic cell death machinery is a hallmark of adenomyosis (39). Among these genes, IGF1 was identified as one of the candidate key regulators to differentiate adenomyosis from endometriosis.…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%
“…No literature exists that specifically addressed the molecular distinction in cases arising from adenomyosis. PIK3-AKT-mTOR and the CTNNB1 signalling pathways have been linked to endometrioid cancer [5, 6], and genetic and epigenetic alterations affecting these pathways have also been shown in adenomyosis [3, 117]. But while genetic and epigenetic studies have suggested convergence in the mechanisms involved in cancer and adenomyosis, the infrequent occurrence of cancer in adenomyosis may be related to the similarities between adenomyosis and to the basal layer in the endometrium, which is less responsive to steroids [118].…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression profile suggests a role of cancer, cell death and cell cycle networks in adenomyosis [2]. More recently, the expression of microRNA-17 was shown to be significantly increased and mRNA of Phosphatase and Tensin Homolog (PTEN-mRNA) to be reduced in adenomyosis [3]. The gene encoding the PTEN protein has been identified as a tumour suppressor that is mutated in a large number of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…кроме того, патогенетическое значение некоторых молекул микроРНк было установлено в ряде экспериментальных иссле-дований. Например, в условиях эксперимента in vitro было показано, что miR-17 активно экс-прессируется в клетках патологического эндо-метрия и подавляет экспрессию онкосупрес-сорного белка PTEn, что стимулирует развитие заболевания [30]. В другом исследовании, авто-ры которого использовали функциональный in vitro тест (Transwell assays), была доказана роль miR-10a в формировании инвазивного фенотипа клеток эндометрия [31].…”
Section: диагностический потенциал микрорнк при эндометриозеunclassified